SPECIFICITY OF THE LEARNING PROCESS IN THE OPEN VIRTUAL LEARNING ENVIRONMENTS (VLE) - Nataliya B. Strekalova (Высшее образование в России)
The article discusses the specificity of the learning process that is performed in an open e0 learning environment. An open virtual learning environment (VLE) is treated as an education systemof a special kind. Special attention is made on an open nature of VLE.